On the two-step iterative method of solving frictional contact problems in elasticity - Angelov, Todor A.; Liolios, Asterios A. (Zielona Góra: Uniwersytet Zielonogórski)
A class of contact problems with friction in elastostatics is considered. Under a certain restriction on the friction coefficient, the convergence of the two-step iterative method proposed by P.D. Panagiotopoulos is proved. Its applicability is discussed and compared with two other iterative methods, and the computed results are presented.
Keywords: contact problems with friction; iterative methods